ANALISIS KEPATUHAN WAJIB PAJAK SEBELUM DAN SESUDAH PELAKSANAAN SUNSET POLICY PADA KPP PRATAMA DI LINGKUNGAN KANTOR WILAYAH DIREKTORAT JENDERAL PAJAK JAWA TIMUR II - HIMAWAN SUTANTO, ARIEF Himawan (Jurnal Akuntansi AKUNESA, 2013)
This study aims to analyze how the impact of sunset policy of taxpayer compliance especiallyKPP in Kanwil DJP Jatim II. The data used is the amount of taxpayers and SPT. Dataanalysis technique used is descriptive analysis. The results have shown the amount oftaxpayers and the amount of SPT, experience the difference in the form of an increasebetween before (2005-2007) and after (2009-2011) sunset policy. Finally it can be concludethat the linkage sunset policy implementation in 2008 of taxpayer compliance in Kanwil DJPJatim II DJP is influential on taxpayer compliance.Keywords: sunset policy, taxpayer compliance, the amount of taxpayers, the amount of SPT